HEPCIDIN PADA ANEMIA OF CHRONIC DISEASE - Agustriadi, Ommy; Suega, Ketut (journal of internal medicine, 2006)
Anemia of chronic disease (ACD) induce dysregulation of iron homeostasis. A hallmark of anemia of chronic disease is thedevelopment of disturbances of iron homeostasis, with increased uptake and retention of iron within cells of thereticuloendothelial system (RES), that leads to a diversion of iron from the circulation into storage sites of RES, and decreasedintestinal iron absorption, subsequent limitation of the availability of iron for erythroid progenitor cells, and iron-restrictederythropoiesis. A new small peptide called hepcidin was found. It is strongly suggest that hepcidin play role on the pathogenesisof ACD. Hepcidin expression is induced by inflammation/infection (by lipopolysaccharide and interleukin-6) and iron overloadcondition, it is strongly suggest that hepcidin induced dysregulation of iron homeostasis by inhibit iron efflux from macrophagedan RES (causing iron retention in turn) and decrease intestinal iron absorption. In the aggregate, the increase of hepcidinproduction suppress erythropoiesis by iron starvation strongly suggest that hepcidin is the key mediator of ACD. If hepcidinfollows the pattern of other peptide hormones or cytokines, its actions will be mediated by cell surface receptors. Elucidation ofthe receptor and its transduction pathways should lead to the development of hepcidin antagonists, some of which could be usefulin treatment of ACD, along with it's underlying disease.